Chamber Music : Elizabethan Sonnet-Sequences and the Pleasure of Criticism - Kuin, Roger (Book collections on Project MUSE., 1998)
Arranged somewhat like a sonnet-sequence, in semi-sequential units, Chamber Music can be seen as following two streams. In the first instance, it presents a fresh and original discussion of the major Elizabethan sonnet-sequences: Sidney's Astrophil and Stella, Spenser's Amoretti and Epithalamion, and Shakespeare's Sonnets and Lover's Complaint. The sonnet-sequences are read in tandem with works of modern criticism, including those of Roland Barthes, Michel Riffaterre, Paul Ricoeur, Jacques Derrida, and Umberto Eco. The book is also an experiment in modern (as opposed to postmodern) criticism in which the content of the argument modifies the presentation.